ETHNOGRAPHIC OBSERVATION OF CROSS-CULTURAL EDUCATION OF CHINESE STUDENTS IN MALAYSIA: A COMPREHENSIVE REVIEW - Xiao Jingyuan; Alexander Stark; Nur Azuki Yusuff; Julia Tan Yin Yin; Yu Wei (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This article aims to provide a comprehensive overview of the cross-cultural education status of Chinese students studying in Malaysia. Through in-depth analysis of the cross-cultural adaptation process of these students in Malaysia, the main problems and challenges they encounter in language communication, cultural conflicts, and psychological adaptation are explored. Additionally, this article also reviews the practical experiences and innovative measures of Malaysian universities in cross-cultural education, including curriculum design, cultural exchange activities, and student services. Based on this, targeted suggestions and measures are proposed to help Chinese students better adapt to the cultural environment of Malaysia, thus enhancing the quality and effectiveness of cross-cultural education. This research is not only significant for promoting the personal growth and international perspective expansion of Chinese students, but also provides valuable references and insights for Malaysian universities to improve cross-cultural education.